Teknik Supervisi Pendidikan dalam Meningkatkan Kualitas Pengajaran di Sekolah - Fathimah, Meti; Ahmadi, Fauzan; Saifudin, MH. (TSAQOFAH, 2025)
This paper explains the techniques of educational supervision in improving the quality of teaching in schools. Among the important roles of supervision are supervising educational activities, correcting deficiencies and errors in the educational process, helping teachers develop their potential optimally, fostering teachers to better understand the purpose of education and helping teachers prepare students to become effective members of society. The purpose of this paper is to explain some educational supervision techniques that can be used to improve the quality of teaching in schools. The research method used in this study uses the library research method, which is research based on processed manuscripts (manuscript studies), facts and primary and secondary data (supporting data) related to the focus of the research. The results of this study indicate that educational supervision techniques are essentially a way to improve the quality of teaching. Teaching supervision ultimately leads to improved student learning outcomes. Learners benefit from interesting lessons, clear expectations and strong teacher-learner relationships.